Hudud law: its validity and application in Malaysia (Terengganu and Kelantan) / Hazrina Zainul Azizdin … [et al.] - Zainul Azizdin, Hazrina; Kamardin, Nor Hafiza; Abd. Rahim, Rashidi; Syed Abdullah, Sh. Nurain (Faculty of Law, 2005)
The main aim of this study is to find answers to some of the outstanding questions surrounding Hudud Law and the Islamic Criminal Justice System from the controversy that arose following the former PAS Government of Terengganu's announcement that it wanted to implement Hudud and other Islamic Criminal Laws in the State in 2002. In order to do this, we shall examine the general Quranic provisions in regards to the offences of Hudud, Qisas and Ta 'zir and the specific provisions of Hudud under the Kelantan Islamic Criminal Bill 1993 and the Terengganu Islamic Criminal Enactment 2002. It should be noted that both laws have yet to be implemented, whereby the Kelantan Bill has yet to be passed by the State Legislative Assembly and gazetted as law, and the Teremgganu Enactment has been passed but failed to obtain the Enabling Act from the Federal Parliament to allow its implementation. The main questions that we hope to answer in this research are; firstly, whether or not the statutory interpretations of Hudud are rightfully based on the Quranic provisions. Secondly, whether the implementation of Hudud in Malaysia will be Constitutional; thirdly, whether the implementation of Hudud is feasible in the current local context and finally, whether the offences and punishments prescribed under Hudud are in gross violation of international human right standards. In addition, we shall also be looking at the working models of the implementation of Hudud Laws in other Islamic countries like Pakistan, Saudi Arabia, Iran and Nigeria in order to identify the problems in the implementation of Hudud Laws and its effectiveness in reducing the crime rates in these countries.